LEGAL PROTECTION OF VICTIMS OF TRAFFICKING IN PERSONS IN INDONESIA (A REALITY IN EAST INDONESIA) - Gerald Theodorus Lumban Toruan (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Trafficking in persons is an act that is inhumane and is a serious problem that must be resolved immediately. Indonesia is no longer a transit country but has also become a destination country for shipments and a sending country for victims of trafficking in persons. The mode that can occur in cases of trafficking in persons is through the Indonesian Migrant Workers mode. A person who is a victim of trafficking in persons is usually lured into working abroad with a large income. Trafficking in persons is a form of transnational crime, where there is usually involvement of people abroad and activities that occur across national borders. This research is a qualitative research with the research locus in Kupang, East Nusa Tenggara and also in Jakarta. The purpose of this study is to find out how the process of sending victims of trafficking in persons and the reasons a person becomes a victim of trafficking in persons, and how the law is implemented in Indonesia.